The Effect of Pre-Arbitration Procedural Requirements on Admissibility and Jurisdiction Under UAE Law - ATEEM, SHADY SHERIF (2023)
This dissertation examines the frequency of pre-arbitration procedural mechanisms used in construction contracts in the UAE and their influence on the effectiveness of the arbitration process. Although these methods are designed to improve efficiency, they frequently result in more conflicts, resulting in a complicated legal environment that lacks a definitive structure under UAE law. Legal practitioners and courts have utilised various approaches to interpret these clauses, leading to ambiguity. This research examines a recent significant judgement from the Dubai Court of Cassation which focuses on differentiating between admissibility and jurisdiction, in line with established international practises. This study proposes implementing contractual modifications to enhance the clarity of drafting, ensuring that parties strictly adhere to procedural requirements, and introducing legal provisions to regulate admissibility and jurisdiction. Furthermore, it is important to take into account the rules of institutional arbitration and the authority given to tribunals to suspend proceedings. Potential areas for further research involve investigating the relevant legislation regarding pre-arbitration prerequisites and analysing how they compare to laws governing the validity of arbitration agreements. The paper proposes further examination of the persistence of pre-arbitration circumstances after the termination of a contract, specifically focusing on the distinctiveness of the arbitration agreement. In essence, improving and simplifying pre-arbitration procedures can promote peaceful resolution of conflicts in accordance with international and UAE court practises